The Protection of Cultural Heritage in International Law - Zombory, Katarzyna (International Law From A Central European Perspective, 2022)
International cooperation in cultural heritage protection has developed primarily within the framework of UNESCO, whose pioneering efforts have led to the adoption of five international cultural conventions. The main areas of protection of cultural heritage in contemporary international law include safeguarding of cultural property during war, preventing the illicit trade of cultural property, and protecting the world cultural heritage, understood as tangible (material) and intangible (non-material) manifestations of culture, as well as natural sites. One of the most significant recent developments of international cultural heritage law is the recognition of the human rights dimension of heritage protection, which is closely related to the notion of cultural rights. In Europe, international efforts in the preservation of cultural heritage were initiated under the auspices of the Council of Europe. There is no binding international instrument dedicated exclusively to the protection of cultural property in Central and Eastern Europe. International protection of cultural heritage in this region faces several challenges owing to the region’s turbulent history. The frequent non-coincidence of political boundaries and ethnic boundaries makes the protection of cultural heritage a highly sensitive issue, given the role of cultural heritage in shaping and maintaining national identities.KEYWORDS: cultural heritage, cultural rights, UNESCO, national minorities, indigenous peoples, international law, Central and Eastern Europe